Adaptação de banda desenhada para animação - Moniz, Eduardo Rosa (2023)
This project work aims to present a methodology applied in the execution of an adaptation of a comic to animation, where both were realized by the same author. This dissertation is subdivided in two parts, in the first it’s exposed the most main theoretical notions and in the second it’s a reflection of the practical part, where it’s depicted the work made by the author of this dissertation. The first portion starts with the theme of state of the art, where the project is historically contextualized with the analyses of some of the most remarkable works and artists for comics, animation and other cases resultant of this process of adaptation. In the part it’s also where it’s presented the most important theorical concepts behind these two types of sequential art. So, the second portion of this dissertation explains the method applied by the author during the realization of the animation based on the comic. First, in the pre-production of the comic, starting by the creation of the initial ideas, a narrative, a moodboard and some concept arts. Based on this studies and references, the realization of the comics can go with more ease. Next, the pre-production of the animation, where it’s executed tests to determined the style and other exercises in preparation for the animation, fundamental to achieve a graphism that it’s both suitable to the limitation presented with this project. In this part it’s also composed a storyboard, where the narrative displayed on the comics is converted, so that it can serve as a guide the execution of the animation in an organized and well-structured. With all this preparatory work it’s possible to continue with the realization of the animation in a more controlled environment and without unnecessary mistakes. In the post-production portion, it’s performed a reflection on the adopted process and presented all the advantages and disadvantages of this methodology, working as a guide to everyone who intends to work on a similar project.